Celebrating Howard Watkins' 40th Birthday in Backyard - Watkins, Howard::::::::: (1987)
Evo Bluestein holding violin, Jemmy Bluestein holding banjo and Howard Watkins talking and holding hand microphone Lighted "Cerveza BUD" neon sign in background window